Superstudio 1966-1973: From the World Without Objects to the Universal Grid - Fernando Quesada (Footprint)
The Italian group of architects Superstudio entered the architectural scene in 1966 with the exhibition Superarchitecture, an ironical commentary on cornucopia and the consumption of design objects. Between that show and the publication of a serial project called Life, Education, Ceremony, Love, Death in 1973, they developed a thorough critique of design and the professional role of architects in information society. This essay traces the development of Superstudio’s critical project, the evolution of their formal repertoire and their operative instruments, studying their designs, projects and texts.